2003
DOI: 10.1242/jeb.00216
|View full text |Cite
|
Sign up to set email alerts
|

Acutely altered hemodynamics following venous obstruction in the early chick embryo

Abstract: SUMMARYIn the venous clip model specific cardiac malformations are induced in the chick embryo by obstructing the right lateral vitelline vein with a microclip. Clipping alters venous return and intracardiac laminar blood flow patterns,with secondary effects on the mechanical load of the embryonic myocardium. We investigated the instantaneous effects of clipping the right lateral vitelline vein on hemodynamics in the stage-17 chick embryo. 32 chick embryos HH 17 were subdivided into venous clipped (N=16) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 28 publications
5
58
0
Order By: Relevance
“…response to hypoxia noted in fetal and adult vertebrates and is consistent with published data in the early embryo (10,13,14,18,24,28,35,36). In contrast to the mid-and lategestation fetus, the early embryo does not compensate for impaired CV function by adjusting HR.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…response to hypoxia noted in fetal and adult vertebrates and is consistent with published data in the early embryo (10,13,14,18,24,28,35,36). In contrast to the mid-and lategestation fetus, the early embryo does not compensate for impaired CV function by adjusting HR.…”
supporting
confidence: 90%
“…In the current study, we tested the hypothesis that hypoxia alters both embryonic ventricular and vascular function and growth in the early embryo during the critical period of early morphogenesis when changes in ventricular and arterial function can produce permanent structural and functional alterations (12,13,24,(27)(28)(29). In response to chronic hypoxia from the onset of incubation, we noted decreased ventricular systolic function, increased arterial impedance, reduced arterial blood flow, and reduced embryo growth and survival.…”
Section: Discussionmentioning
confidence: 88%
“…However, defects in aortic arch patterning may also be a consequence of abnormal cardiovascular hemodynamics resulting from vitelline vein and liver congestion. For example, obstruction of the vitelline vein with a microclip can induce cardiac malformations in the chick embryo (Stekelenburg-de Vos et al, 2003). However, given the broad expression of MRTF-B and the results of our MRTF-B ⌬/⌬ mutant mice analysis, it is likely that MRTF-B has important roles in multiple tissues.…”
Section: Mrtf-bmentioning
confidence: 93%
“…In a previous study using a 20 MHz Doppler velocity meter, we have demonstrated that the experimental alteration of venous return caused by venous clipping has major acute effects on hemodynamics in the HH stage 17 chick embryo (3,8). Peak systolic velocity, peak blood flow, and SV are all significantly decreased for up to 5 h after clipping.…”
mentioning
confidence: 87%
“…The intricate relationship between hemodynamics and cardiac morphogenesis has been a major study topic in this model. The venous clip model is an intervention model for the chick embryo in which permanent obstruction of the right lateral vitelline vein temporarily reduces the mechanical load on the embryonic myocardium and induces a spectrum of outflow tract anomalies (3). This model was designed to obtain insight into the effects of altered venous return patterns on cardiac morphogenesis and malformations (4).…”
mentioning
confidence: 99%